2020
DOI: 10.1063/5.0030738
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical thermal transport in nanoconfined water

Abstract: The structure of nanoconfined fluids is particularly non-uniform owing to the wall interaction, resulting in the distinctive characteristic of thermal transport compared to bulk fluids. We present the molecular simulations on the thermal transport of water confined in nanochannels with a major investigation of its spatial distribution under the effects of wall interaction. The results show that the thermal conductivity of nanoconfined water is inhomogeneous and its layered distribution is very similar to the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These vacancies gradually reduce with the increase of ρ A and the linear increase of thermal conductivity of confined water. The increase in thermal conductivity can be attributed to the increasing heat flux carrier, namely, the increasing number of water molecules in the channel, which has been fully discussed in previous literature …”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…These vacancies gradually reduce with the increase of ρ A and the linear increase of thermal conductivity of confined water. The increase in thermal conductivity can be attributed to the increasing heat flux carrier, namely, the increasing number of water molecules in the channel, which has been fully discussed in previous literature …”
Section: Discussionmentioning
confidence: 82%
“…The increase in thermal conductivity can be attributed to the increasing heat flux carrier, namely, the increasing number of water molecules in the channel, which has been fully discussed in previous literature. 27 Afterward, if more water molecules are put in the channel, a large-scale ordered quadrilateral structure is formed (see Figure 2c) just like a fishing net, which is called structure SII. This near-square symmetry structure can be demonstrated by the structure factor of the confined water corresponding to the case of ρ A = 12.5 nm −2 shown in Figure 2d, which is comparable to the structure of confined water from previous studies.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also revealed that the thermal energy is less effectively transferred through the first adsorption layer near the wall than that in the central region. Recently, Zhao et al [19] presented the molecular simulations on the thermal transport of water confined in nanochannels. They also found the inhomogeneous profiles of thermal conductivity, which is nearly in phase with the density profile.…”
Section: Introductionmentioning
confidence: 99%